(untitled) (Damascus University Journal of agriculture sciences, 2026)
. The research was conducted with the aim of studying the allelopathic effect of leaf powders of the sweet potato plant, Ipomea batatas (L.) Lam. and sunflower, Helianthus annuus L. and banana, Musa lutea Valmayor (L.) and the effect of some herbicides (paraquat, glyphosate, 2,4-D, rimsulfuron, linuron, metribuzin, halosulfuron methyl and haloxyfop) and the synergistic effect of powders with reduced doses of pesticides in Chlorophyll of purple nutsedge, Cyperus rotundus L. growing with maize crop, Zea mays L.. Treatment with sunflower powder did not reduce chlorophyll, while the powders of the other plants gave significant effects on the amounts of chlorophyll A, as the sweet potato powder led to a significant reduction of 16.06% during the first week and 7.99 during the second week and 25.35 as a total decrease during 15 days after treatment, while the percentages in the banana powder treatment were 19.57, 8.19 and 29.37%, respectively. The results also demonstrated the ineffectiveness of the pesticide Haloxyfop, while the rest of the pesticides significantly reduced the percentages of chlorophyll and were (75.93, 73.32, 57.64, 43.2, 28.64, 21.54 and 17.38%) for the pesticides paraquat, halosulfuron, rimsulfuron, glyphosate, 2,4-D, Linuron and metribuzin, respectively, when using the recommended concentrations. The performance of these pesticides improved when urea fertilizer was added a week before spraying the pesticide, so the reduction rates for the previous pesticides became 80.24, 84.41, 70.07, 57.5, 47.41, 32.38 and 27.41%. The best treatment with a negative effect on the amount of chlorophyll B was the halosulfuron methyl treatment (half recommended doses) with the powder of the three species with urea, with a decrease rate of 64.44%. While the best treatment in affecting total chlorophyll was the paraquat treatment with the powder of the three species and urea by a decrease of 86.72%, followed by the treatment of glyphosate with the powder of the three species and urea by a decrease of 85.80%. This indicates the utmost importance of combining allelopathic plant residues with herbicides. The best pesticides that had a negative effect on the chlorophyll A/B ratio were paraquat pesticide treatment (-13.1), then halosulfuron methyl pesticide (-11.58) and rimsulfuron pesticide (10.27). Therefore, these pesticides can be preferred to combat this herb.